Penyuluhan Kesehatan Tentang Gout Arthritis dan Pembuatan Obat Non Farmakologi dengan Jus Nanas dan Madu di Desa Purwodadi Kecamatan Tonjong Kabupaten Brebes - Ahmad Zakiudin; Tati Karyawati; Ahmad Akhyarudin (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Gout arthritis (gout) is a disease that occurs suddenly and repeatedly, characterized by the formation of monosodium uric acid crystal deposits that attack the joints, due to high levels of uric acid in the blood (hyperuricemia). The aim of this activity is to be able to understand gouty arthritis and the practice of making non-pharmacological drugs from pineapple juice and honey to reduce uric acid levels in the body. This health education can increase the knowledge of Purwodadi village residents to do their best to treat gout arthritis using traditional medicine. Health education for residents can increase knowledge and skills in using simple traditional medicines